Attitude development from the perspectives of occupational therapy interns and clinical educators - Medallon, Kim Gerald (The Journal of Practice Teaching and Learning, 2023)
Background: Attitude development is a component in the training of occupational therapy interns. Little attention is given to this construct in the Philippines. Purpose: This study aims to identify demonstrated professional behaviours, determine their consistency and extent of manifestation, and identify enablers and barriers. Method: This study utilized a qualitative design using observations, interviews, and review of documents. Interns and clinical educators from a private university participated in this study. Descriptive and content thematic analyses were utilized. Findings: The demonstrated professional behaviors were considered narrow in scope. Most of the identified enablers and barriers were external to training. They provide the strongest influence to the interns. Implications: Instructional modifications need to be made in order to deliberately target this component in service delivery. Key words: behavior, professional practice, teaching